1988
DOI: 10.1159/000177414
|View full text |Cite
|
Sign up to set email alerts
|

Hypocholesterolaemic Effects of Dietary Propionate: Studies in Whole Animals and Perfused Rat Liver

Abstract: In adult male rats fed a non-purified diet supplemented with 5 % sodium propionate, plasma cholesterol concentrations were significantly depressed. Although liver cholesterol was increased by feeding propionate, rates of hepatic cholesterol and fatty acid synthesis were unchanged. Tissue concentrations and rates of synthesis of cholesterol were also unaffected by dietary propionate in stomach, small intestine and caecum. Concentrations of propionate in hepatic portal venous plasma were raised by feeding the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1
2

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(55 citation statements)
references
References 15 publications
3
49
1
2
Order By: Relevance
“…[Fung et al, 2012]. Moreover, acetate and propionate which are also signifi cantly increased in the present study can differentially infl uence fat metabolism; acetate seems to promote lipogenesis in the liver, whereas propionate has been reported to inhibit this process [Nishina & Freedland, 1990;Demigné et al, 1995], however, there are strong evidences suggesting that the inhibitory effect of propionate is rather unlikely [Illman et al, 1988]. In the present study, the intensifi cation of SCFA synthesis in group A resulted in just slightly lowered pH value of the caecal digesta and signifi cantly lowered pH of the colon digesta.…”
Section: Discussionmentioning
confidence: 44%
“…[Fung et al, 2012]. Moreover, acetate and propionate which are also signifi cantly increased in the present study can differentially infl uence fat metabolism; acetate seems to promote lipogenesis in the liver, whereas propionate has been reported to inhibit this process [Nishina & Freedland, 1990;Demigné et al, 1995], however, there are strong evidences suggesting that the inhibitory effect of propionate is rather unlikely [Illman et al, 1988]. In the present study, the intensifi cation of SCFA synthesis in group A resulted in just slightly lowered pH value of the caecal digesta and signifi cantly lowered pH of the colon digesta.…”
Section: Discussionmentioning
confidence: 44%
“…Illman et al have also reported that white wheat flour lowered the plasma cholesterol concentration in rats. 23) We found that the bile acid concentration in the fecal excretion and SCFA in the cecum of the BBP group were both higher than in the other two groups. These results show that the sugar beet fiber might have influenced the cholesterol metabolism in the large intestine.…”
Section: Discussionmentioning
confidence: 60%
“…The proposed mechanisms for lipid modulation by low-GI foods compared to high GI foods may include: (1) lower insulin-stimulated HMG-CoA reductase activity (the ratelimiting enzyme in cholesterol synthesis; Rodwell et al, 1976), as a result of a reduced rate of carbohydrate absorption; (2) impaired bile acid and cholesterol reabsorption from the ileum due to the typically high fibre content of low-GI foods (Kritchevsky & Story 1974;Jenkins et al, 1993); (3) inhibition of hepatic cholesterol synthesis by the short chain fatty acid propionate, a by-product of colonic fermentation (Illman et al, 1988;Wolever et al, 1988;Wright et al, 1990); (4) reduced inflammatory response. Some evidence suggests a possible role of insulin in stimulating acute-phase proteins (O'Riordain et al, 1995;Thompson et al, 1991) which have been directly related to intra-abdominal fat and inversely related to insulin-stimulated glucose disposal (Sites et al, 2002).…”
Section: The Glycemic Index In Coronary Heart Diseasementioning
confidence: 99%